An Individual-Based Approach to Mapping Safety Culture in the Manufacturing Sector: A Case Study at PT MNO - Hernanda Melia Cholis; Dwi Hartanti (Greenation Research & Yayasan Global Resarch National, 2025)
This study aims to evaluate the safety culture in the manufacturing sector through an individual-based approach using the Attitude-Behaviour-Culture Model and the Risk Type Compass to map employees' risk characteristics.. The company studied is PT MNO, a manufacturing company in West Java with a high accident rate in its production division. This approach identifies attitudes, behaviors, and values that contribute to the formation of a safety culture. Data were collected using a questionnaire distributed to 51 employees in the production division, with 37 responses received. The results indicate that the majority of employees exhibit conservative (prudent) and analytical (deliberate) risk characteristics, which foster a systematic and compliant safety culture. However, this culture tends to be less flexible in adapting to fast-changing work environments. The study recommends strengthening attitude-based training, providing psychological support to reduce anxiety, and developing emergency decision-making procedures to create a more adaptive and innovative safety culture. These findings provide valuable insights for enhancing safety risk management in the manufacturing sector.